Новый этап в истории развития процессуального права Совета Европы - Анцупова, Татьяна Александровна; Анцупова, Тетяна Олександрівна; Ancupova, Tat'jana (My University, 2009)
In a frame of this article it were investigated some actual legal questions, wich appear because of reforming European Court of Human Rights. It is defined the main changes and novels as to organizarion of it's work in accordance to Protocol No. 14 and Protocol No. 14 bis amending the Convention's supervisory system. It is analised the main reasons of adoption and the main results of entering into forse of Protocol No. 14 bis. Also analised the participanse of the Ukraine in reforms of ECHR.
Анцупова Т. А. Новый этап в истории развития процессуального права Совета Европы / Т. А. Анцупова // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 233-241.
Keywords: Совет Европы; Европейский суд по правам человека (ЕСПЧ); реформирование контрольного механизма ЕКПЧ; Протокол № 14 к ЕКПЧ; Протокол № 14 bis к ЕКПЧ; Рада Європи; Європейський суд з прав людини (ЄСПЛ); реформування контрольного механізму ЄКПЛ; Протоколо № 14 до ЄКПЛ; Протокол № 14 bis до ЄКПЛ; The Council of Europe; European Court of Human Rights (ECHR); the formation of the control mechanism of the ECHR; Protocol number 14 to the ECHR; Protocol number 14 bis to the ECHR